Anatomical Arrangement Reconstruction of Anal Canal Parts via Plasty of the Ligament of Parks in Stage IV Hemorrhoids - A. A. Kartashev; A. L. Charyshkin (Креативная хирургия и онкология)
Introduction. Stage III and IV hemorrhoids involve the destruction of the ligament of Parks and disruption in the anatomical arrangement of anal canal parts, which makes reconstruction procedures particularly relevant. Materials and methods. Patients were assigned to two groups. The first group included 35 patients who underwent hemorrhoidectomy according to the proposed method, while the second included 32 patients who underwent open hemorrhoidectomy (Milligan-Morgan). HDSS and SHSHD questionnaires were used to assess the quality of life.Results. Complete epithelialization of wounds was observed at day 37.90 ± 9.49 in the first group and at day 47.80 ± 17.40 in the second group, p = 0.022. Group 2 patients exhibited significantly greater persistence of node prolapse symptoms: 0.46 ± 0.51 on the prolapse scale, as compared to 0.05 ± 0.22 in Group 1.Discussion. Hemorrhoidectomy constitutes a safe and effective procedure; therefore, it is impossible to significantly improve its results; however, we can correct certain aspects of this intervention.Conclusion. As compared to the conventional method, the proposed method of hemorrhoidectomy allows the wound healing time to be reduced from 47.80 ± 17.40 days to 37.90 ± 9.49 days without affecting the risk of postoperative complications. Three months after conventional hemorrhoidectomy, the number of patients retaining mucosal prolapse phenomena, which lead to a decrease in the quality of life, is 0.46 ± 0.5 on the “prolapse” scale; when applying the developed method, their number is significantly lower and tends to zero (0.05 ± 0.22 on the “prolapse” scale).